PENGABDIAN KEPADA MASYARAKAT USAHA KERIPIK SINGKONG “NYAMEN” RASA ORIGINAL (SPINNER MACHINE) - Yudi Oktriadi; Masdani Masdani; Achmad Afriadi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Cassava chips are one of the typical light food products that are favored by valious levels of society. In the process of making cassava chips, many processes that are passed in the form of slicing cassava into thin, fried, dried/ drained, mixed with seasonings and as well as packaging. From a survey that has been carried out on partners, the drying process of cassava chips after frying is the main problem because the drying process still uses manual which is left to dry on an existing container and the drying process takes approximately 5-10 minutes with the number of chips being dried 2 -3 kg and done draining a lot of time. From this problem, as the proponent of the Educational Institution will make a cassava chip spice spinner machine that can replace human labor, so that capacity and time can be increased. Partners will get appropriate technology in the form of a cassava chip spinner machine and training on the process of using the machine and maintaining the machine. In addition, Partners will always receive maintenance services if the machine provided is disturbed or damaged. To achieve this goal, the Partners and the Service team agreed to propose to increase the quality and production capacity. The development of the production process is carried out by providing cassava chips dryer/spinner machine technology. With this machine, the results achieved with a total of 10 kg dried cassava chips in 10 minutes are met. So in conclusion, with the machine, partners can develop their business because they can meet market demand.